The ivory industry in Botswana - Martin, Esmond (Pachyderm, 1984)
Botswana’s ivory manufacturing industry began in 1975 with Botswana Game Industries (BGI) as the first commercial company. A high percentage of the finished ivory products were exported. The trade led to increased elephant poaching especially in the northern part of the country forcing the animals to seek refuge in sanctuaries. The Chobe National Park and Moremi Wildlife Reserve attracted great numbers which have in turn caused large scale vegetation destruction. The effects of elephant predation was a concern to many and led to the commencement of a research project in 1983. In the meantime, all elephant hunting was stopped. The article addresses issues that the Department of Wildlife, National Parks and Tourism should take up to reduce poaching and bring to halt the illegal trade in ivory.